Wnt signalling modulates transcribed-ultraconserved regions in hepatobiliary cancers. Issue 7 (12th September 2016) - Carotenuto, Pietro; Fassan, Matteo; Pandolfo, Rosantony; Lampis, Andrea; Vicentini, Caterina; Cascione, Luciano; Paulus-Hock, Viola; Boulter, Luke; Guest, Rachel; Quagliata, Luca; Hahne, Jens Claus; Ridgway, Rachel; et al.
Abstract : Objective: Transcribed-ultraconserved regions (T-UCR) are long non-coding RNAs which are conserved across species and are involved in carcinogenesis. We studied T-UCRs downstream of the Wnt/β-catenin pathway in liver cancer. Design: Hypomorphic Apc mice ( Apcfl/fl ) and thiocetamide (TAA)-treated rats developed Wnt/β-catenin dependent hepatocarcinoma (HCC) and cholangiocarcinoma (CCA), respectively. T-UCR expression was assessed by microarray, real-time PCR and in situ hybridisation. Results: Overexpression of the T-UCR uc.158− could differentiate Wnt/β-catenin dependent HCC from normal liver and from β-catenin negative diethylnitrosamine (DEN)-induced HCC. uc.158− was overexpressed in human HepG2 versus Huh7 cells in line with activation of the Wnt pathway. In vitro modulation of β-catenin altered uc.158− expression in human malignant hepatocytes. uc.158− expression was increased in CTNNB1 -mutated human HCCs compared with non-mutated human HCCs, and in human HCC with nuclear localisation of β-catenin. uc.158− was increased in TAA rat CCA and reduced after treatment with Wnt/β-catenin inhibitors. uc.158− expression was negative in human normal liver and biliary epithelia, while it was increased in human CCA in two different cohorts. Locked nucleic acid-mediated inhibition of uc.158− reduced anchorage cell growth, 3D-spheroid formation and spheroid-based cell migration, and increased apoptosis in HepG2 and SW1 cells. miR-193b was predicted to have binding sites within the uc.158− sequence. Modulation of uc.158− changed miR-193b expression in human malignant hepatocytes. Co-transfection of uc.158− inhibitor and anti-miR-193b rescued the effect of uc.158− inhibition on cell viability. Conclusions: We showed that uc.158− is activated by the Wnt pathway in liver cancers and drives their growth. Thus, it may represent a promising target for the development of novel therapeutics.